2022
DOI: 10.1136/jitc-2021-004157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 vaccination on the use of PD-1 inhibitor in treating patients with cancer: a real-world study

Abstract: Anti-COVID-19 vaccination may have functional implications for immune checkpoint inhibitor treatment in patients with cancer. This study was undertaken to determine whether the safety or efficacy of anti-PD-1 therapy is reduced in patients with cancer during COVID-19 vaccination. A large multicenter observational study was conducted in 83 Chinese hospitals between January 28, 2021 and September 30, 2021. A total of 3552 patients were screened and 2048 eligible patients with cancer receiving PD-1 inhibitor trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
(15 reference statements)
2
24
0
Order By: Relevance
“…Mei et al, speculated that giving the COVID-19 vaccine and anti-PD1 therapy within close temporal proximity of each other may enhance co-stimulatory and reduce co-inhibitory regulation, accounting for the increase in mild AEs in vaccinated patients. Additionally, they also speculated that this increase in immune response allows for the chemotherapy to work more effectively, consistent with their finding of vaccinated patients having higher disease control rates [ 66 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Mei et al, speculated that giving the COVID-19 vaccine and anti-PD1 therapy within close temporal proximity of each other may enhance co-stimulatory and reduce co-inhibitory regulation, accounting for the increase in mild AEs in vaccinated patients. Additionally, they also speculated that this increase in immune response allows for the chemotherapy to work more effectively, consistent with their finding of vaccinated patients having higher disease control rates [ 66 ].…”
Section: Discussionsupporting
confidence: 64%
“…Mei et al, compared 1518 vaccinated cancer patients (288 with one dose, 1134 with two doses, 96 with three doses) receiving camrelizumab alone or in conjunction with other therapies to unvaccinated patients. Compared with matched unvaccinated patients, a statistically greater percentage of vaccinated patients had mild AE ≤ 2 (33.8% vs. 19.8%; p < 0.001) following camrelizumab treatment [ 66 ].…”
Section: Safety Of the Covid-19 Vaccines On The Cancer Patientsmentioning
confidence: 99%
“…A recently published multicenter observational study included 2048 patients who had previously received anti-PD-1 therapy and were divided into vaccinated subgroup (receiving inactivated SARS-CoV-2 virus vaccine) and non-vaccinated subgroup for comparison. Both subgroups were similar in terms of ICIs efficacy, while in terms of safety, the vaccinated subgroup was more likely to have mild irAE, while the incidence of severe irAE was instead reduced ( 167 ). Although case of cytokine release syndrome occurring 5 days after BTN162b2 mRNA COVID-19 vaccination in patient with long-term anti-PD-1 therapy have been reported ( 168 ), the benefit-risk profile still strongly supports vaccination in cancer patients.…”
Section: Medication Strategies For Icis Under the Covid-19 Pandemicmentioning
confidence: 99%
“…Anti-PD-1 treatment was demonstrated to be effective in nasopharyngeal cancer (NPC) patients 1 . During the COVID-19 pandemic, concern was raised whether anti-PD-1 treatment can interfere with COVID-19 vaccination in NPC patients, although our previous study showed that the efficacy and safety of anti-PD-1 treatment was not reduced in general cancer patients vaccinated with SinoVac 2 . NPC affects the upper respiratory tract, where the COVID-19 infection takes place.…”
mentioning
confidence: 99%